2019
DOI: 10.3390/nu12010016
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Composition of the Pediatric Gut Microbiome: A Systematic Review

Abstract: The consortium of trillions of microorganisms that live inside the human gut are integral to health. Little has been done to collate and characterize the microbiome of children. A systematic review was undertaken to address this gap (PROSPERO ID: CRD42018109599). MEDLINE and EMBASE were searched using the keywords: “healthy preadolescent children” and “gut microbiome” to 31 August 2018. Of the 815 journal articles, 42 met the inclusion criteria. The primary outcome was the relative abundance of bacteria at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 122 publications
(154 reference statements)
0
23
1
Order By: Relevance
“…Moreover, a recent systematic review, characterizing the composition of the pediatric gut microbiome, fixed the relative abundance of this family at ca. 16.8% [113]. Since the aim of this review was to evaluate the changes referred to disease in comparison with healthy controls, any exclusion criteria (e.g., the sequencing methods, the selection of regions used for the taxonomic assignment, and the type of samples) were applied to assess the relative abundance in healthy subjects.…”
Section: Lachnospiraceae In Healthmentioning
confidence: 99%
“…Moreover, a recent systematic review, characterizing the composition of the pediatric gut microbiome, fixed the relative abundance of this family at ca. 16.8% [113]. Since the aim of this review was to evaluate the changes referred to disease in comparison with healthy controls, any exclusion criteria (e.g., the sequencing methods, the selection of regions used for the taxonomic assignment, and the type of samples) were applied to assess the relative abundance in healthy subjects.…”
Section: Lachnospiraceae In Healthmentioning
confidence: 99%
“… 91 In a systematic review, Lachnospiraceae were shown to be a dominant family in older children of 8 years and older. 93 This age-related colonization by the Lachnospiraceae family would suggest that it is not commonly passed to the infant at birth via vertical transmission.…”
Section: The Sporobiota Of the Infant Gutmentioning
confidence: 99%
“…A large number of studies on the 16S rDNA sequence have shown that the human intestinal tract is mainly composed of the phyla Bacteroidetes and Firmicutes, although there are trillions of microorganisms live in it (Torres-Fuentes et al, 2017). In addition to analyzing microbial composition, 16s rDNA sequencing can also be utilized to measure microbial diversity, which is a measure of the number, type and evenness of the gut microorganisms (Deering et al, 2019). Therefore, changes in intestinal microbiota in diseased individuals can be assessed by analyzing the microbial composition and diversity, and exploring the relationship between microorganisms and the host.…”
Section: Introductionmentioning
confidence: 99%